2017
DOI: 10.19044/esj.2017.v13n9p1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Patterns and Plasmid Profiles of Staphylococcus Aureus Isolated from Different Clinical Specimens in Saudi Arabia

Abstract: The aims of this study were to investigate antibiotic resistance patterns and plasmid profile of antibiotic resistant Staphylococcus strains isolated from clinical specimens, and to find out a possible relationship between plasmids profile and antibiotic sensitivity patterns. Staphylococcus strains were isolated from different clinical specimens from different hospitals and primary health care centers. Antimicrobial susceptibility of Staphylococcus isolates was determined using disc diffusion method against 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
2
4
2
Order By: Relevance
“…Conversely, the lowest resistance rates were against piperacillin-tazobactam and amikacin. Similar results have been documented in Saudi Arabia [60] and Pakistan [29]. Significant decreases in Proteus spp.…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, the lowest resistance rates were against piperacillin-tazobactam and amikacin. Similar results have been documented in Saudi Arabia [60] and Pakistan [29]. Significant decreases in Proteus spp.…”
Section: Discussionsupporting
confidence: 87%
“…Many researchers have addressed the relationship between plasmid profiles and antibiotic resistance patterns in both Gram-positive and Gram-negative bacteria in an attempt to find correlations between the number of plasmids found and the type of antibiotic resistance. In our previous study on S. aureus, we did not find any correlation between the number of plasmids found and the pattern of resistance (Jaran, 2017); other studies on Gram-negative E. coli and Salmonella spp. also showed no direct correlation between the number of plasmids found and resistance patterns (Jaran, 2015;2016).…”
Section: Resultscontrasting
confidence: 62%
“…This result is in agreement with the studies ofMwajuma (2010) who reported that Bacillus subtilis, Escherichia coli, K. pneumoniae and Micrococcus luteus were resistant to ceftriaxone, ampiclox, erythromycin and zinnacef. Similarly,Mbim et al (2016), Jaran, (2015 andTagoe et al (2011) reported the existence of multidrug resistance in E. coli, S. aureus and B. subtilis. Generally, the development of drug resistant pathogens can be linked to indiscriminate use of antibiotics and resultant selective pressure on bacteria(Mohammed et al, 2014).…”
mentioning
confidence: 89%